Civic Committee for the Restoration of Cracow Heritage: origin, experience, programme - Krasnowolski, Bogusław (Protection of Cultural Heritage, 2017)
The Committee (acronym: SKOZK) was established in 1978, following listing Krakow as a world heritage site. It fulfilled expectations from the past, when heritage assets were damaged by industrial pollution and state ideology curtailed financing of works on sacred and private grounds. An undoubted strength of the early time was the recognition of Krakow heritage protection as a matter of state importance, while the domination of political circumstances remained a weakness. The political transformation of 1989/90 changed the environment: SKOZK was now dominated by heritage preservation milieus, and members were appointed by the President of the Republic of Poland, and his Chancellery provided a major part of financial means. As grants generally cover up to 50% of the cost, the fund has a stimulating role as beneficiaries need to find sources for matching funds. Since 1990, the Committee’s activity has concentrated on the most valuable complexes: Wawel, the historical centre of the city, former town of Kazimierz with Jewish quarter, and the most treasurable enclaves situated on the outskirts of the city. Achievements of SKOZK include development of a model for cooperation between private (NGO) and public (central and territorial authorities) sectors, definition of strategic goals, and a priority of the ensuing tasks.